DESIGN OF ROBUST TRIAXIAL SYSTEMS FOR STABILIZATION OF AIRBORNE OBSERVATION EQUIPMENT - Sushchenko, Olga (Proceedings of National Aviation University (archive), 2014)
The state space model of the stabilization plant, which represents a platform with observation equipment and measuring instruments installed in the triaxial gimbals, is developed. The approach to the robust structural synthesis based on the method of the mixed sensitivity is considered. The algorithm of the robust discrete controller design is shown. The synthesized controller structure in the form of the quadruple of state space matrices and the simulation results are represented.